UJI VIGOR GULMA ECHINOCHLOA CRUSS-GALLY TERHADAP BERBAGAI ALELOPATI TUMBUHAN - Risvan Anwar; Eka Suzanna; Yarmadi Yarmadi (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2013)
This research was aimed to select allelopathy of the seven species of plants that are supposed to reduce the vigor of weeds Echinochloa crus-galli. The research was conducted in the Laboratory of Plantation Protection Bereau Bengkulu Province from January to March 2011. This research was arranged in Completely Randomized Design with five replications. The treatments was alelopati extract consisted of control (pure water), Chromolaena odorata, Lantana camara, Acasia mangium, Swietania macrophylla, Pithecollobium jiringa, Eucalyptus sp and Cocos nucifera. The results showed that the allelopathy treatment reduced significantly the weed Echinochloa crus-galli vigor. All of the allelopathy treatment made 0% germinating of weed Echinochloa crus-galli, however control (without allelopathy) made 78% germination.